Myanmar Military Forces Atrocities Against the Rohingya under International Criminal Law - Ogiandhafiz Juanda (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The Rohingya, a Muslim ethnic minority group living in northern Rakhine State, Western Myanmar, are considered among the most persecuted minorities in the world. The Rohingya People have been subjected to a variety of significant violations and human rights abuses as a result of their lack of citizenship. They are victims of a series of massacres and inhumane treatment committed by Myanmar military forces, such murder, kidnapping, rape, force labour, torture, extrajudicial executions, restrictions on movements, forced eviction and house and land destruction. In the previous ten years, several crackdowns on the Rohingya people in Rakhine have caused them to flee to neighboring countries. This article examines the atrocities committed by Myanmar military forces against the Rohingya people under international law, notably from the standpoint of international criminal law definition of crimes against humanity